Development of a Mobile Multipurpose Cooking System Integrated with a Cooling Storage and Washing Sink - Awotoye, B.A.; Abolarin, M.S.; Lawal, S.S.; Maruf, K.A. (UNIABUJA Journal of Engineering and Technology (UJET), 2025)
Street food vendors and outdoor food services in many regions face challenges of poor hygiene, inefficient energy use, and lack of integrated systems for cooking, washing, and cooling, leading to health risks, operational inefficiencies, and environmental concerns. This research aims to develop a mobile, multipurpose cooking system integrated with cooling storage and a washing sink to enhance efficiency, hygiene, and convenience for outdoor events, mobile food services, and emergency response situations. The system was designed and fabricated using locally sourced materials, prioritizing energy efficiency and ease of use. The cooking unit, powered by LPG, underwent a comprehensive water boiling test. The results demonstrated a thermal efficiency of 77.3% and a specific fuel consumption of 0.072 kg/kJ, highlighting the unit’s effective fuel utilization and performance. The roasting unit, which utilizes charcoal as the energy source, was tested by roasting corn. The experiment revealed that an average of 1.002 kg of 9 corn cobs were roasted in 6 minutes using approximately 0.636 kg of charcoal. The roasting unit achieved a thermal efficiency of 90.5%, indicating efficient heat utilization. Performance evaluations of the system underscored its high efficiency, fuel economy, and rapid cooking and roasting rates. The integration of cooling storage and a washing sink further enhances its practicality and versatility, making it an ideal solution for a wide range of applications, including outdoor events, mobile food services, and emergency scenarios. The successful design and fabrication of this system demonstrate the potential for locally sourced materials used in creating innovative and efficient cooking solutions.